Runaway electron energy determination by angular distribution of Cherenkov radiation; Journal of Instrumentation; Vol. 15 : Radiation from Relativistic Electrons in Periodic Structures (RREPS-19) - Alekseev B. A. Boris Alexandrovich; Konkov A. S. Anatoly Sergeevich; Baksht E. Kh. Evgeny Khaimovich; Erofeev M. V. Mikhail Vladimirovich; Potylitsyn A. P. Alexander Petrovich; Shevelev M. V. Mihail Viktorovich; Tarasenko V. F. Victor Fedotovich; Vukolov A. V. Artem Vladimirovich (2020, 2020)
Title screen